Role of yoga in psychological correlates of learning ability in school children - Manasi Bera; Atin Kumar Barik; Tushar Kanti Bera (Wolters Kluwer Medknow Publications, 2017)
Background: The art of learning may contribute to various skills required for better performance in human abilities involving memory, learning (attention fluctuation, sentence completion, and general intelligence), perception, motor functions, etc. Objective: This experiment was conducted to evaluate the efficacy of yoga training intervention toward improvement in the selected psychological correlates of learning ability among the school children. Method: A parallel group, research design was considered in this experiment, which was conducted on sixty male students (n = 60), age group of 12-14 years, who were randomly assigned into two identical groups (Group A: exp group and Group B: control) and each group consists of thirty students. The research design includes pretest, yoga training, mid-test, detraining, and posttest. The variables of learning abilities (viz., attention fluctuation, sentence completion, and general intelligence) were tested three times (pre-, mid-, and post-) using standard methods. The yoga training intervention comprising prayer recitation, Yoga Asanas, Anuloma Viloma (Pranayama), and Omkar Chanting was imparted for 45 min daily in the morning (except Sundays and holidays) for a total period of 45 days, whereas the controlled students were kept busy with recreation and library readings. Then, mid-test was conducted. Further, the detraining phase (Phase II) was considered for the next 45 days, and then posttest was conducted. Thus, total duration of the experiment was 90 days. Statistical Analysis: All statistical analyses were carried out by 2 × 3 × 3 factorial ANOVA followed by Scheffe's post hoc test. Result: The results revealed that Hatha Yogic practices lead to the reduction in attention fluctuation which implies improvement in attention ability among the school children. Further, improvement in sentence completion ability and general intelligence was evident after yoga training intervention. Moreover, detraining phase of 6 weeks could maintain similar trend of results as compared to the controlled subjects. Conclusion: Hatha Yogic practices lead to a significant improvement in the selected correlates of better learning ability in school children.